1993
DOI: 10.1002/jez.1402670216
|View full text |Cite
|
Sign up to set email alerts
|

Spiral patterns in the micropylar wall and filaments on the chorion in eggs of the medaka, Oryzias latipes

Abstract: The relationship between spiral patterns in the inner wall of the micropyle and attaching and non-attaching filaments on the chorion was investigated by electron microscopy in eggs of the medaka, Oryzias latipes. There were both right-and left-handed spiral patterns of attaching filaments that arose from the chorion at the vegetal pole area. In the majority of eggs examined, however, the prominent folds in the inner wall of the micropylar vestibule descended toward the micropylar canal in a left-handed spiral.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…As reported in the previous study [12], the animal-vegetal axis of medaka oocytes is first recognized by the unilateral bending of the nonattaching filaments prior to the initiation of vitellogenesis. The polarity of small pre-vitellogenic (St. V) oocytes seems to be determined by the formation of the VPA.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As reported in the previous study [12], the animal-vegetal axis of medaka oocytes is first recognized by the unilateral bending of the nonattaching filaments prior to the initiation of vitellogenesis. The polarity of small pre-vitellogenic (St. V) oocytes seems to be determined by the formation of the VPA.…”
Section: Discussionsupporting
confidence: 61%
“…As described elsewhere [12], rotation of the oocyte must cause bending of the attaching and non-attaching filaments that are directly in contact with the basement membrane, and the bending must be in the direction opposite to that of the rotation. When the rotation was disturbed by impaling the oocytes with glass needles at right angles to the oocyte axis, the bending direction or the shape of the attaching and non-attaching filaments was altered, as seen in Figs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…3d). Several authors have reported that, until the initiation of oocyte maturation, the micropylar canal is plugged with cytoplasmic protrusion of a large, mushroomshaped micropylar cell (Takano and Ohta 1982;Kobayashi and Yamamoto 1985;Iwamatsu et al 1993b;Nakashima and Iwamatsu 1994). Bodies of the micropylar cell and nearby granulosa cells exert mechanical pressure on the external surface of the growing oocyte and thus participate in the formation of the micropylar vestibule.…”
Section: Discussionmentioning
confidence: 98%
“…Histological analyses revealed the presence of filaments located on the chorionic surface of vitellogenic oocytes. Other species [e.g, Oryzias latipes (Temminck and Schlegel) and Odontesthes bonariensis (Valenciennes), Iwamatsu & Keino 1978; Iwamatsu 1992; Iwamatsu et al. 1993; Guandalini et al.…”
Section: Discussionmentioning
confidence: 99%